Modified copper-zinc-aluminum catalyst as well as preparation method and application thereof

Through the preparation method of modified copper-zinc-aluminum catalyst, the problems of low conversion and low selectivity when the isooctanol is converted to isooctanaldehyde are solved, and higher conversion and selectivity are achieved, meeting the needs of industrial production.

CN119524861AActive Publication Date: 2025-02-28NINGBO CESTOIL ADVANCED MATERIAL CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510088423.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-02-28
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

When the commercially available copper-zinc-aluminum catalysts catalyzed to isooctanol, the conversion rate is low and the selectivity is low, making it difficult to meet industrial needs.

Method used

The preparation method of modified copper-zinc-aluminum catalyst is adopted to construct a complex and stable multi-layer structure by three precipitation, combining the introduction of a double aluminum source and the impregnation treatment of sodium nitrate or magnesium nitrate solution to improve the specific surface area of ​​the catalyst and the uniform distribution of active components.

Benefits of technology

It significantly improves the stability and catalytic efficiency of the catalyst, enhances the conversion rate of isooctanol and the selectivity of isooctanol, and meets the demand for efficient catalytic conversion in industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the field of catalyst materials, in particular to a modified copper-zinc-aluminum catalyst and a preparation method and application thereof. The invention relates to a preparation method of a modified copper-zinc-aluminum catalyst, which comprises the following steps: preparing zinc nitrate and aluminum nitrate into a salt solution a, preparing a first precipitator into an alkali solution b, and preparing hydrotalcite precipitates from the two solutions; copper nitrate, zinc nitrate and aluminum nitrate are prepared into a salt solution A, a second precipitator is prepared into an alkali solution B, and the two solutions are prepared into a second precipitate; reacting and aging the hydrotalcite precipitate and alpha-aluminum oxide with the second precipitate to prepare a precursor; and dipping the precursor in a sodium nitrate or magnesium nitrate solution, and finally respectively preparing the Na modified copper-zinc-aluminum catalyst and the Mg modified copper-zinc-aluminum catalyst. By adopting a three-time precipitation mode and introducing double aluminum sources, the stability and the catalytic efficiency of the catalyst are improved; the dipping treatment of the sodium nitrate or magnesium nitrate solution improves the activity of the catalyst in the organic alcohol conversion reaction and the selectivity of the organic aldehyde.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of catalyst materials, and specifically to a modified copper-zinc-aluminum catalyst and a preparation method and application thereof. Background Art

[0002] Organic acids are important chemical raw materials. For example, 2-ethylhexanoic acid and its derivatives are widely used in coatings, inks, medicines, plastics, petroleum and other industries. Among them, the application scale in coatings is the largest, accounting for more than 50%. In recent years, with the increasingly widespread application of 2-ethylhexanoic acid in the coatings industry, petroleum industry and other fields, the domestic demand for 2-ethylhexanoic acid has continued to grow.

[0003] At present, the industrial production of isooctyl acid mainly adopts the alkaline oxidation method with isooctyl alcohol as raw material. In actual production, the alkaline oxidation method produces a lot of salt-containing wastewater, consumes a lot of oxidants, and causes a large amount of three wastes to be discharged, which has a great impact on the environment.

[0004] In order to adopt a more environmentally friendly approach, it is advisable to prepare isooctyl acid from isooctyl alcohol by a two-step process. That is, isooctyl alcohol undergoes hydrogen transfer dehydrogenation reaction under the action of a catalyst to generate isooctyl aldehyde, which is separated and purified to obtain the intermediate product isooctyl aldehyde, and then isooctyl aldehyde reacts with oxygen under the action of a catalyst to generate isooctyl acid. This will be an environmentally friendly new process.

[0005] Copper-zinc-aluminum catalysts are widely used in various organic chemical reactions, such as hydrogenation, oxidation and cracking. In actual application, the copper-zinc-aluminum catalysts currently available on the market have poor effects on catalytic conversion of isooctyl alcohol to isooctyl aldehyde, which is manifested in low conversion rate of isooctyl alcohol and low selectivity of isooctyl aldehyde, thus limiting the production of isooctyl aldehyde and making it difficult to meet people's needs. Summary of the invention

[0006] In order to solve the problem that commercially available copper-zinc-aluminum catalysts are less effective in catalyzing the conversion of isooctyl alcohol into isooctyl aldehyde, the present application provides a modified copper-zinc-aluminum catalyst and a preparation method and application thereof. The modified copper-zinc-aluminum catalyst has higher organic aldehyde selectivity and organic alcohol conversion rate than commercially available copper-zinc-aluminum catalysts.

[0007] In the first aspect, the present application provides a method for preparing a modified copper-zinc-aluminum catalyst, using the following technical solution: A method for preparing a modified copper-zinc-aluminum catalyst, the specific preparation steps comprising: (1) Weigh zinc nitrate and aluminum nitrate and dissolve them to prepare salt solution a; (2) dissolving the precipitant to prepare an alkaline solution b; the first precipitant comprises a mixture of sodium carbonate and sodium hydroxide; (3) mixing the salt solution a and the alkaline solution b, centrifuging, washing and drying after the reaction to obtain a hydrotalcite precipitate; (4) Weigh copper nitrate, zinc nitrate and aluminum nitrate and dissolve them in water to obtain salt solution A; (5) dissolving a second precipitant in water to prepare an alkaline solution B; the second precipitant comprises one of sodium carbonate, sodium bicarbonate and sodium hydroxide; (6) the salt solution A and the alkaline solution B are flowed together into a reaction container containing deionized water, wherein the pH value in the reaction container is in the range of 6.0-6.5, to obtain a reaction solution containing a second precipitate; (7) After the second precipitate is stabilized, the hydrotalcite precipitate and α-alumina obtained in step (3) are added to the reaction solution containing the second precipitate obtained in step (6) to continue aging; (8) After aging is completed, the precipitate is filtered, washed and dried to obtain a precursor; the precursor is immersed in a sodium nitrate or magnesium nitrate solution, and then rotary evaporated, dried and roasted to obtain a roasted product; (9) The calcined product is uniformly mixed with graphite to obtain a mixture, and the mixture is pressed into tablets to obtain Na-modified copper-zinc-aluminum catalyst and Mg-modified copper-zinc-aluminum catalyst, respectively.

[0008] By adopting the above technical solution, this method is carried out by three precipitation steps, firstly precipitating Zn 2+ and Al 3+ The initial hydrotalcite structure is formed (steps 1-3), followed by the overall precipitation of Cu 2+ 、Zn 2+ 、Al 3+ (Steps 4-6), and cleverly introduce α-alumina in the final stage (Step 7). This step-by-step and dual aluminum source (initial nitrate and subsequent α-alumina) introduction strategy helps to build a more complex and stable multi-level structure. Such a structure not only increases the specific surface area of ​​the catalyst, but also promotes the uniform distribution of active components, thereby improving the stability and catalytic efficiency of the catalyst.

[0009] The Zn-Al hydrotalcite precipitate formed in the early stage serves as a substrate, providing good support for the subsequent Cu, Zn, and Al secondary precipitates. This secondary precipitation on a high specific surface area substrate allows the active components to be dispersed more evenly, avoiding the problem of particle agglomeration caused by excessive local concentration. At the same time, the high specific surface area helps the rapid adsorption and activation of reactant molecules, accelerating the catalytic reaction rate.

[0010] The α-alumina introduced in the final stage not only serves as a physical support but also improves the overall thermal stability of the catalyst through its stable chemical properties.

[0011] The precursor was impregnated with sodium nitrate or magnesium nitrate solution to further regulate the surface chemical properties of the catalyst. The introduction of these cations may improve the activity of the catalyst in the organic alcohol conversion reaction and the selectivity of organic aldehydes by changing the surface charge distribution, enhancing acid-base synergy or forming new active centers. In addition, the impregnation treatment may also promote the formation of micropores on the catalyst surface, which is beneficial to the rapid mass transfer of reactants and products.

[0012] Preferably, in steps (1) and (2), the solvents of the salt solution a and the alkaline solution b include water, a first mixed solvent of water and isopropanol, and a second mixed solvent of water, n-hexane and isopropanol.

[0013] Preferably, the solvent of the salt solution a and the alkaline solution b is a second mixed solvent of water, n-hexane and isopropanol.

[0014] By adopting the above technical scheme, when organic matter (such as n-hexane, isopropanol) and water are used as mixed solvents, a water-in-oil (W / O) microemulsion can be formed under appropriate conditions. In this microemulsion, tiny water droplets are surrounded by the organic continuous phase, forming tiny reaction spaces. This microemulsion structure provides an extremely high specific surface area and a uniform microenvironment, which is conducive to the uniform dispersion of reactants and the improvement of reaction rate.

[0015] During the hydrotalcite precipitation process, since the reactants exist in the form of water-in-oil, tiny water droplets act as "microreactors" to promote the nucleation and growth of hydrotalcite nanosheets. Since these nanosheets grow in a confined manner in the microemulsion, they tend to form thinner and more dispersed structures, which significantly increases the specific surface area of ​​the final product. High specific surface area is one of the key factors in catalyst performance because it provides more adsorption and activation sites for reactants, promoting the catalytic reaction.

[0016] The microemulsion structure in the organic-water mixed solvent system also promotes the uniform growth of catalyst precursors (such as hydrotalcite). In the microemulsion, the reactant molecules and the generated product molecules can be well dispersed, avoiding agglomeration and uneven growth caused by excessive local concentration. This uniform growth mode is conducive to the preparation of catalyst precursors with excellent pore structure and surface properties.

[0017] By increasing the specific surface area and uniformity of hydrotalcite, the thermal stability and catalytic activity of subsequent catalysts can be further improved. A high specific surface area means that more active sites are exposed to the reactants, which is beneficial to the catalytic reaction. At the same time, the uniform pore structure and surface properties also help to improve the heat resistance and anti-sintering ability of the catalyst, so that it can still maintain good catalytic performance under high temperature conditions.

[0018] Preferably, in step (1), the zinc nitrate Zn2+ Al with aluminum nitrate 3+ The molar ratio is 5:1-2:1.

[0019] By adopting the above technical solution, hydrotalcite (LDHs) is a type of layered double hydroxide, and its structural stability is closely related to the charge balance of interlayer ions. Zn 2+ and Al 3+ As the layer cation, its molar ratio directly affects the number and type of interlayer anions, and thus affects the overall stability of LDHs. When the added Zn / Al molar ratio deviates from the range of 5:1 to 2:1, it may cause interlayer charge imbalance and affect the stability of LDHs. The structural characteristics of LDHs determine the arrangement of its layer cations. Zn 2+ and Al 3+ Due to the different ionic radius and charge, their distribution and arrangement in the hydrotalcite layer need to meet a certain ratio to maintain the stability and flatness of the layer. Too high or too low Zn / Al molar ratio may destroy this arrangement, resulting in the distortion or collapse of the LDHs structure.

[0020] Zn 2+ and Al 3+ In hydrotalcite, Zn not only serves as a structural component, but also as an active site for catalytic reactions. Their molar ratio directly affects the number and distribution of active sites, and thus the catalytic performance of the catalyst. Too high or too low a Zn / Al molar ratio may lead to insufficient or uneven distribution of active sites, reducing the catalytic efficiency of the catalyst. In some catalytic reactions, Zn 2+ and Al 3+ The ratio of Zn to Al also affects the selectivity of the catalyst. By adjusting the Zn / Al molar ratio, the adsorption and conversion capacity of the catalyst for specific reactants can be optimized, and the selectivity and purity of the product can be improved.

[0021] Preferably, the molar ratio of Al content among the aluminum nitrate in step (1), the aluminum nitrate in step (4) and the α-alumina in step (7) is 1:1:1.

[0022] By adopting the above technical scheme, hydrotalcite (LDHs) is a type of double metal hydroxide with a layered structure, and the cations on its layer plates (such as Zn 2+ 、Al 3+ ) and interlayer anions are bound to each other through electrostatic interaction. Keeping the Al content in the hydrotalcite precipitate and the second precipitate relatively consistent helps maintain the stability and integrity of the LDHs layered structure. In LDHs, charge balance needs to be maintained between cations and anions. By adjusting the Al content, it can be ensured that interlayer anions (such as CO3 2- 、NO3 -The number and type of cations (e.g., etc.) match those of the laminar cations, thus maintaining the overall charge neutrality of LDHs.

[0023] The Al element in hydrotalcite is not only a structural component, but also may serve as an active site for catalytic reactions. Maintaining an appropriate Al content ratio can ensure that the catalyst has sufficient active sites, thereby improving the efficiency and selectivity of the catalytic reaction. After mixing α-alumina with hydrotalcite, the Al element is more evenly distributed between the two. This uniform distribution helps to exert the synergistic effect between different components and further improve the overall performance of the catalyst.

[0024] In a second aspect, the present application provides a modified copper-zinc-aluminum catalyst, which adopts the following technical solution: A modified copper-zinc-aluminum catalyst is prepared by the above preparation method.

[0025] By adopting the above technical scheme, the technical advantages of the modified copper-zinc-aluminum catalyst over the prior art are the same as those of the above preparation method, which will not be repeated here.

[0026] In a third aspect, the present application provides an application of a modified copper-zinc-aluminum catalyst, using the following technical solution: The invention discloses an application of a modified copper-zinc-aluminum catalyst, which is an application of the modified copper-zinc-aluminum catalyst in catalyzing the preparation of organic aldehydes from organic alcohols.

[0027] By adopting the above technical scheme, the modified copper-zinc-aluminum catalyst of the present application can be used for catalytic application in the production processes of methanol to formaldehyde, ethanol to form acetaldehyde, isooctyl alcohol to form isooctyl aldehyde, etc.

[0028] Preferably, the use of the modified copper-zinc-aluminum catalyst comprises the following steps: Initial dehydrogenation: preheating the organic alcohol and adding it to the first dehydrogenation reactor for dehydrogenation, adding a modified copper-zinc-aluminum catalyst into the first dehydrogenation reactor to obtain an initial dehydrogenation product; Re-dehydrogenation: separating the initial dehydrogenation product into gas and liquid, and then transferring the liquid into a second dehydrogenation reactor for dehydrogenation, adding a modified copper-zinc-aluminum catalyst into the second dehydrogenation reactor to obtain a re-dehydrogenation product; Distillation: The re-dehydrogenation product is distilled to obtain an organic aldehyde.

[0029] By adopting the above technical solution, most of the easily dehydrogenated hydrogen atoms can be effectively removed during the initial dehydrogenation, generating some organic aldehydes and other intermediates. After the initial dehydrogenation product is separated into gas and liquid, the liquid part enters the second dehydrogenation reactor for further dehydrogenation. In this stage, the remaining catalyst is used to further deepen the dehydrogenation reaction, and the remaining hydrogen atoms are completely removed, thereby generating higher purity organic aldehydes. The two-stage dehydrogenation process allows independent control of the reaction conditions of each stage, such as temperature, pressure, catalyst dosage, etc. This flexibility helps to optimize the reaction efficiency of each stage while reducing the generation of by-products.

[0030] The catalyst is used in two stages of the reaction, and can be optimized according to the reaction characteristics of each stage. This can not only ensure the activity of the catalyst, but also improve the service life and utilization rate of the catalyst. By segmented dehydrogenation, side reactions caused by excessively violent reactions or improper reaction conditions can be reduced. Each stage of the reaction can be fine-tuned as needed to ensure the efficiency of the main reaction. After two stages of dehydrogenation and distillation, high-purity organic aldehydes can be obtained. This is crucial for subsequent reactions or product applications.

[0031] Preferably, the modified copper-zinc-aluminum catalyst added in the initial dehydrogenation step is a Na-modified copper-zinc-aluminum catalyst, and the modified copper-zinc-aluminum catalyst added in the re-dehydrogenation step is a Mg-modified copper-zinc-aluminum catalyst.

[0032] By adopting the above technical scheme, the Na-modified copper-zinc-aluminum catalyst has a high selectivity for organic aldehydes. In the initial dehydrogenation stage, the organic alcohol just begins to undergo a dehydrogenation reaction, and at this time, the catalyst is required to effectively guide the reaction to the direction of generating organic aldehydes and reduce the generation of by-products. The high selectivity of the Na-modified catalyst ensures that relatively pure organic aldehydes and other valuable intermediates can be obtained at this stage.

[0033] The Mg-modified copper-zinc-aluminum catalyst has a higher organic alcohol conversion rate while maintaining a certain selectivity. In the re-dehydrogenation stage, the remaining organic alcohol in the initial dehydrogenation product needs to be further converted into organic aldehydes. The high conversion rate of the Mg-modified catalyst can ensure the efficiency of this process and reduce the unreacted organic alcohol residue.

[0034] Since the re-dehydrogenation stage needs to process a partially dehydrogenated mixture, which may contain some intermediates or stable compounds that are difficult to dehydrogenate, the Mg-modified catalyst may have a stronger deep dehydrogenation ability and can further convert these compounds into organic aldehydes.

[0035] The application of two different types of catalysts in two different dehydrogenation stages can produce a synergistic effect. The high-purity organic aldehydes and other intermediates generated in the initial dehydrogenation stage can serve as good substrates for the re-dehydrogenation stage, while the Mg-modified catalyst can fully utilize these substrates for deep conversion.

[0036] Preferably, the mass ratio of the Na-modified copper-zinc-aluminum catalyst to the Mg-modified copper-zinc-aluminum catalyst is 1-3:1.

[0037] By adopting the above technical scheme, since the organic aldehyde selectivity of the Na-modified copper-zinc-aluminum catalyst is high, the conversion effect of the organic alcohol is low. The organic aldehyde selectivity of the Mg-modified copper-zinc-aluminum catalyst is low, and the conversion effect of the organic alcohol is high. Therefore, putting more Na-modified copper-zinc-aluminum catalyst in the first dehydrogenation reactor and putting less Mg-modified copper-zinc-aluminum catalyst in the second dehydrogenation reactor is more appropriate. Of course, the Na-modified copper-zinc-aluminum catalyst in the first dehydrogenation reactor cannot be put too much, otherwise the conversion rate of the organic alcohol will be reduced.

[0038] In summary, this application has the following beneficial effects: 1. Since the present application adopts a three-precipitation method and the introduction of a dual aluminum source, it is helpful to construct a more complex and stable multi-level structure, increase the specific surface area of ​​the catalyst, and promote the uniform distribution of active components, thereby improving the stability and catalytic efficiency of the catalyst; the precursor is impregnated with a sodium nitrate or magnesium nitrate solution to achieve further regulation of the surface chemical properties of the catalyst, which may improve the activity of the catalyst in the organic alcohol conversion reaction and the selectivity of the organic aldehyde by changing the surface charge distribution, enhancing the acid-base synergy or forming new active centers; 2. When organic matter (such as n-hexane, isopropanol) and water are used as mixed solvents in the present application, a water-in-oil (W / O) microemulsion can be formed under appropriate conditions, which significantly increases the specific surface area of ​​the final product and promotes the catalytic reaction; 3. In the present application, the Na-modified copper-zinc-aluminum catalyst is added to the first dehydrogenation reactor, and the Mg-modified copper-zinc-aluminum catalyst is added to the second dehydrogenation reactor, which can fully utilize the high aldehyde selectivity of the Na-modified catalyst, guide the organic alcohol reaction to the direction of generating organic aldehydes, and reduce the generation of by-products; in the re-dehydrogenation stage, the Mg-modified copper-zinc-aluminum catalyst further converts the remaining organic alcohol in the initial dehydrogenation product into organic aldehydes, thereby reducing the unreacted organic alcohol residues. DETAILED DESCRIPTION

[0039] The raw materials in this application include the following parts: Zinc nitrate: a commercially available product with CAS number 7779-88-6; Aluminum nitrate: a commercially available product with CAS number 13473-90-0; Copper nitrate: a commercially available product with CAS number 10402-29-6; The first precipitant includes a commercial product of sodium carbonate with a CAS number of 497-19-8 and a commercial product of sodium hydroxide with a CAS number of 1310-73-2; Second precipitant: The precipitant of the present application includes sodium carbonate, sodium bicarbonate and sodium hydroxide. The present application takes the commercially available sodium carbonate product with CAS No. 497-19-8 as an example; Deionized water: Use commercially available product with CAS number 7732-18-5; α-alumina: commercially available products; Sodium nitrate: a commercially available product with CAS number 7631-99-4; Magnesium nitrate: a commercially available product with CAS number 10377-60-3; n-Hexane: a commercial product with CAS number 110-54-3 was used; Isopropyl alcohol: a commercially available product with CAS number 67-63-0 is used; Graphite: a commercially available product with CAS number 7782-42-5 was used; The present application is further described in detail below in conjunction with embodiments and comparative examples.

[0040] Example 1 A method for preparing a reaction liquid phase product comprises the following steps: (1) 0.04 mol of Zn(NO3)2 and 0.01 mol of Al(NO3)3 were dissolved in 600 mL of a mixed solvent consisting of 200 mL of water, 200 mL of n-hexane and 200 mL of isopropanol to form a salt solution a; (2) 0.05 mol of NaCO3 and 0.15 mol of NaOH were dissolved in 600 mL of a mixed solvent consisting of 200 mL of water, 200 mL of n-hexane and 200 mL of isopropanol to form a salt solution b; (3) After mixing the salt solution a and the alkaline solution b, ultrasonically treat the mixture at room temperature for 30 minutes, separate the mixture using a centrifuge, wash the mixture with ethanol for 5 times, and dry the mixture to obtain a hydrotalcite precipitate; (4) Dissolve 0.15 mol of Cu(NO3)2, 0.24 mol of Zn(NO3)2 and 0.01 mol of Al(NO3)3 in 500 mL of deionized water, dissolve by ultrasonication, and stir to fully dissolve to form salt solution A; (5) Dissolve 0.40 mol of NaCO3 in 2000 mL of deionized water and stir to fully dissolve it to form the alkaline solution B required for precipitation; (6) Under strong stirring, salt solution A and alkaline solution B are simultaneously added dropwise into a reaction tank containing 500 mL of deionized water, wherein the pH value in the reaction tank is in the range of 6.0-6.5, to obtain a reaction solution containing a second precipitate; (7) After the second precipitate is stably formed for 15 minutes, all the above hydrotalcite precipitates and 0.005 mol of α-alumina are added, the reaction temperature of the reaction tank is controlled to 80°C with a water bath, and the reaction is aged at a constant temperature for 2 hours; (8) After aging is completed, filter and wash the precipitate with deionized water until there is no Na + The obtained precipitate was dried at 120°C for 12 h to obtain a precursor; (9) 98 g of the precursor was immersed in 100 mL of sodium nitrate solution (sodium nitrate content was 2 g), then rotary evaporated, dried at 120 °C for 12 h, and then calcined at 500 °C at a rate of 5 °C / min for 6 h to obtain a calcined product; 97 g of the calcined product was mixed with 3 g of graphite to obtain a mixture, and the mixture was pressed into tablets to obtain a Na-modified copper-zinc-aluminum catalyst; (10) 98 g of the precursor was immersed in 100 mL of magnesium nitrate solution (magnesium nitrate content was 2 g), then rotary evaporated, dried at 120 °C for 12 h, and then calcined at 500 °C at a rate of 5 °C / min for 6 h to obtain a calcined product; 97 g of the calcined product was evenly mixed with 3 g of graphite to obtain a mixture, and the mixture was pressed into tablets to obtain a Mg-modified copper-zinc-aluminum catalyst.

[0041] An application of a modified copper-zinc-aluminum catalyst comprises the following steps: Initial dehydrogenation: 1000mL of isooctyl alcohol (the modified copper-zinc-aluminum catalyst of the present application can be used in catalyzing the preparation of organic aldehydes from organic alcohols, such as methanol to formaldehyde, ethanol to acetaldehyde, isooctyl alcohol to isooctyl aldehyde, etc., and the present application uses isooctyl alcohol as an example) is preheated to 220°C and added to the first dehydrogenation reactor for dehydrogenation. The dehydrogenation operating conditions are: temperature 280°C, operating pressure 0.1Mpa, space velocity 10h -1 , dehydrogenation for 3h, adding 20g of Na-modified copper-zinc-aluminum catalyst into the first dehydrogenation reactor to obtain an initial dehydrogenation product; Re-dehydrogenation: The initial dehydrogenation product is separated into gas and liquid after passing through the gas-liquid separation tank, and then the liquid is transferred to the second dehydrogenation reactor for dehydrogenation. The dehydrogenation operating conditions are: temperature 230℃, pressure 0.1Mpa, space velocity 10h -1 , dehydrogenation for 3h, adding 10g of Mg-modified copper-zinc-aluminum catalyst into the second dehydrogenation reactor to obtain a re-dehydrogenation product; Distillation: The re-dehydrogenation product is transferred to a distillation tower for distillation, isooctyl aldehyde is obtained from the side line, and the contents of isooctyl alcohol and isooctyl aldehyde in the reaction liquid phase product are detected.

[0042] Example 2-3 Example 2 Based on the application of Example 1, 20 g of Na-modified copper-zinc-aluminum catalyst was added to the first dehydrogenation reactor, and 10 g of Na-modified copper-zinc-aluminum catalyst was added to the second dehydrogenation reactor, and other conditions remained unchanged.

[0043] Example 3 Based on the application of Example 1, 20 g of Mg-modified copper-zinc-aluminum catalyst was added to the first dehydrogenation reactor, and 10 g of Mg-modified copper-zinc-aluminum catalyst was added to the second dehydrogenation reactor, and other conditions remained unchanged.

[0044] Example 4 Based on the application of Example 1, 20 g of Mg-modified copper-zinc-aluminum catalyst was added to the first dehydrogenation reactor, and 10 g of Na-modified copper-zinc-aluminum catalyst was added to the second dehydrogenation reactor, and other conditions remained unchanged.

[0045] Comparative Example 1-2 Comparative Example 1 is based on the application of Example 1, and only initial dehydrogenation is performed. 30 g of Mg-modified copper-zinc-aluminum catalyst is added to the first dehydrogenation reactor, and dehydrogenation is performed for 6 hours to obtain an initial dehydrogenation product. The initial dehydrogenation product is passed through a gas-liquid separation tank for gas-liquid separation, and then the liquid is transferred to a distillation tower for distillation, isooctyl aldehyde is obtained from the side line, and the contents of isooctyl alcohol and isooctyl aldehyde in the reaction liquid phase product are detected.

[0046] Comparative Example 2 Based on the application of Example 1, 20 g of commercially available copper-zinc-aluminum catalyst was added to the first dehydrogenation reactor, and 10 g of commercially available copper-zinc-aluminum catalyst was added to the second dehydrogenation reactor, while other conditions remained unchanged.

[0047] Table 1 Performance test table of Examples 1-4 and Comparative Examples 1-2

[0048] Performance testing The reaction liquid phase products of Examples 1-4 and Comparative Examples 1-2 were subjected to the following performance tests, and the test results are shown in Table 1.

[0049] Aldehyde selectivity and alcohol conversion The yields of isooctyl alcohol and isooctyl aldehyde in the liquid phase product of the above reaction were detected. The mass contents of isooctyl aldehyde and isooctyl alcohol were measured by gas chromatography FID detector. The chromatographic column was FFAP (30*0.33*0.32) polar column. The test conditions were heating from 60°C, heating rate of 6°C / min, heating to 190°C and keeping for 8 minutes. The calculation can be obtained: Isooctyl aldehyde selectivity = isooctyl aldehyde mass content in the reaction liquid phase product / (1-isooctyl alcohol mass content in the reaction liquid phase product) × 100%.

[0050] Isooctyl alcohol conversion rate = (1-mass content of isooctyl alcohol in the liquid product after reaction) × 100%.

[0051] Referring to Table 1, by comparing Examples 1-4 and Comparative Examples 1-2, it can be seen that compared with Comparative Example 1, the isooctyl alcohol conversion rates of Examples 1-4 are much higher than those of Comparative Example 1, indicating that the two-stage dehydrogenation is more conducive to the conversion of isooctyl alcohol than the one-stage dehydrogenation, which may be because the two-stage dehydrogenation helps to optimize the reaction efficiency of each stage, thereby improving the isooctyl alcohol conversion rate.

[0052] Compared with Comparative Example 2, the isooctyl alcohol conversion rates of Examples 1-4 are all higher than those of Comparative Example 2, indicating that the catalytic conversion effect of the modified copper-zinc-aluminum catalyst prepared in the present application on isooctyl alcohol is higher than that of the commercially available copper-zinc-aluminum catalyst. The isooctyl aldehyde selectivity of Examples 1-2 and 4 is higher than that of Comparative Example 2, and the isooctyl aldehyde selectivity of Example 3 is slightly lower than that of Comparative Example 2, indicating that the isooctyl aldehyde selectivity of the Na-modified copper-zinc-aluminum catalyst is better than that of the commercially available copper-zinc-aluminum catalyst, and the isooctyl aldehyde selectivity of the Mg-modified copper-zinc-aluminum catalyst is comparable to that of the commercially available copper-zinc-aluminum catalyst.

[0053] Comparison of Examples 1-4 shows that the selectivity of isooctylaldehyde of the Na-modified copper-zinc-aluminum catalyst is better than that of the Mg-modified copper-zinc-aluminum catalyst, and the catalytic conversion effect of the Mg-modified copper-zinc-aluminum catalyst on isooctyl alcohol is better than that of the Na-modified copper-zinc-aluminum catalyst. Comparison shows that Example 1 has the best comprehensive effect, and Example 1 is preferred.

[0054] Embodiment 5-6 In Example 5-6, based on the application of Example 1, the sum of the masses of the Na-modified copper-zinc-aluminum catalyst added to the first dehydrogenation reactor and the Mg-modified copper-zinc-aluminum catalyst added to the second dehydrogenation reactor is controlled to be 30 g, and the mass ratio of the Na-modified copper-zinc-aluminum catalyst added to the first dehydrogenation reactor and the Mg-modified copper-zinc-aluminum catalyst added to the second dehydrogenation reactor is adjusted. The specific adjustment is shown in Table 2.

[0055] The reaction liquid phase product of Example 5-6 was subjected to the above performance test, and the test results are shown in Table 2.

[0056] Table 2 Performance test table of Example 1 and Example 5-6

[0057] Referring to Table 2, it can be seen from Comparative Example 1 and Example 5-6 that due to the high selectivity of isooctylaldehyde of Na-modified copper-zinc-aluminum catalyst, the conversion effect to isooctyl alcohol is low. The selectivity of isooctylaldehyde of Mg-modified copper-zinc-aluminum catalyst is on the low side, and the conversion effect to isooctyl alcohol is high. Therefore, more Na-modified copper-zinc-aluminum catalyst is put into the first dehydrogenation reactor, and less Mg-modified copper-zinc-aluminum catalyst is put into the second dehydrogenation reactor, and such selection is more appropriate. Of course, Na-modified copper-zinc-aluminum catalyst can not be put too much in the first dehydrogenation reactor, otherwise the conversion rate of isooctyl alcohol will be reduced. By comparison, the mass ratio between the Na-modified copper-zinc-aluminum catalyst and the Mg-modified copper-zinc-aluminum catalyst of Example 1 is better.

[0058] Embodiment 7-9 Example 7 Based on the preparation method of Example 1, the solvents in steps (1) and (2) were adjusted to 300 mL of water and 300 mL of n-hexane, and the other conditions remained unchanged.

[0059] Example 8 Based on the preparation method of Example 1, the solvents in steps (1) and (2) were adjusted to 300 mL of water and 300 mL of isopropanol, and the other conditions remained unchanged.

[0060] Example 9 Based on the preparation method of Example 1, the solvent in steps (1) and (2) was adjusted to 600 mL of water, and the other conditions remained unchanged.

[0061] The reaction liquid phase products of Examples 7-9 were subjected to the above performance tests, and the test results are shown in Table 3.

[0062] Table 3 Performance test table of Example 1 and Examples 7-9

[0063] Referring to Table 3, by comparing Example 1 with Examples 7-9, it can be seen that the solvent in steps (1) and (2) is a mixture of an organic solvent and water, which is more conducive to the present application. This may be because in a system with organic matter and water as a mixed solvent, an oil-in-water (W / O) microemulsion or microcapsule structure can be formed by controlling the conditions. This structure provides a unique microenvironment for the formation of hydrotalcite, which is conducive to the growth and dispersion of hydrotalcite crystals. The tiny water droplets in the oil-in-water structure act as a "microreactor" for the growth of hydrotalcite, which can significantly increase the nucleation density and growth rate of hydrotalcite, thereby generating hydrotalcite with a higher specific surface area. This high specific surface area hydrotalcite can provide more favorable growth sites in the subsequent preparation of catalysts, thereby improving the activity and selectivity of the catalyst.

[0064] In comparison, the solvent formulation method adopted in Example 1 is more beneficial to the present application.

[0065] Examples 10-13 Example 10-13 Based on the preparation method of Example 1, the addition amounts of zinc nitrate and aluminum nitrate in step (1) are adjusted so that Zn 2+ and Al 3+ The molar ratio of is adjusted, and the specific adjustment is shown in Table 4.

[0066] The reaction liquid phase products of Examples 10-13 were subjected to the above performance tests, and the test results are shown in Table 4 respectively.

[0067] Table 4 Zn in the hydrotalcite precipitate in step (3) of Example 1 and Examples 10-13 2+ and Al 3+ Molar ratio and performance test table

[0068] Referring to Table 4, it can be seen from the comparison between Example 1 and Examples 10-13 that as Zn 2+ and Al 3+ As the molar ratio of Zn decreases, the selectivity of isooctyl aldehyde and the conversion rate of isooctyl alcohol both show a trend of first increasing and then decreasing. This may be due to the fact that as Zn 2+ and Al 3+ The molar ratio of hydrotalcite gradually decreases, and the charge between the hydrotalcite layers gradually balances, thereby improving the stability of the hydrotalcite; and the active sites will be distributed more evenly, improving the catalytic efficiency of the catalyst.

[0069] When it exceeds a certain range, the charge between the hydrotalcite layers gradually becomes unbalanced, thereby reducing the stability of the hydrotalcite; and the active sites will gradually become unevenly distributed, reducing the catalytic efficiency of the catalyst.

[0070] Examples 14-16 Examples 14-16 are based on the preparation method of Example 1, and the aluminum nitrate in step (1), the aluminum nitrate in step (4) and the α-alumina in step (7) are adjusted to adjust the molar ratio of the Al element content of the three. The specific adjustment is shown in Table 5.

[0071] Comparative Examples 3-5 Comparative Example 3: Based on the preparation method of Example 1, 0.02 mol of Al(NO3)3 was added in step (1), and Al(NO3)3 was not added in step (4), and other conditions remained unchanged.

[0072] Comparative Example 4 Based on the preparation method of Example 1, 0.005 mol of α-alumina was added in step (1), and α-alumina was not added in step (7), and other conditions remained unchanged.

[0073] Comparative Example 5 Based on the preparation method of Example 1, 0.005 mol of α-alumina was added in step (6), and α-alumina was not added in step (7), and other conditions remained unchanged.

[0074] The reaction liquid products of Examples 14-16 and Comparative Examples 3-5 were subjected to the above performance tests, and the test results are shown in Table 5 respectively.

[0075] Table 5 Molar ratio of Al content and performance test of Example 1, Examples 14-16 and Comparative Examples 3-5

[0076] Referring to Table 5, by comparing Example 1, Examples 14-16 and Comparative Examples 3-5, it can be seen that the selectivity of isooctyl aldehyde and the conversion rate of isooctyl alcohol in both Example 1 and Example 14 are higher than those in Examples 15-16, indicating that keeping the Al content in the hydrotalcite precipitate and the second precipitate relatively consistent helps maintain the stability and integrity of the LDHs layered structure. In addition, mixing α-alumina with hydrotalcite requires the distribution of the Al element between the two. The more uniform the distribution, the more conducive it is to exert the synergistic effect between the different components and further improve the overall performance of the catalyst.

[0077] The selectivity of isooctyl aldehyde and the conversion rate of isooctyl alcohol in Comparative Examples 3-5 are much lower than those in Example 1, indicating that the addition of Al element at each stage is very necessary. Whether it is the Al source added in the formation of hydrotalcite precipitation, the second precipitation or step (7), it cannot be reduced, otherwise it will affect the overall structure of the catalyst and the uniform distribution of the active ingredients.

[0078] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a modified copper-zinc-aluminum catalyst, characterized in that: The specific preparation steps include: (1) Weigh zinc nitrate and aluminum nitrate and dissolve them to prepare salt solution a; (2) dissolving the precipitant to prepare an alkaline solution b; the first precipitant comprises a mixture of sodium carbonate and sodium hydroxide; (3) mixing the salt solution a and the alkaline solution b, centrifuging, washing and drying after the reaction to obtain a hydrotalcite precipitate; (4) Weigh copper nitrate, zinc nitrate and aluminum nitrate and dissolve them in water to obtain salt solution A; (5) dissolving a second precipitant in water to prepare an alkaline solution B; the second precipitant comprises one of sodium carbonate, sodium bicarbonate and sodium hydroxide; (6) the salt solution A and the alkaline solution B are flowed together into a reaction container containing deionized water, wherein the pH value in the reaction container is in the range of 6.0-6.5, to obtain a reaction solution containing a second precipitate; (7) After the second precipitate is stabilized, the hydrotalcite precipitate and α-alumina obtained in step (3) are added to the reaction solution containing the second precipitate obtained in step (6) to continue aging; (8) After aging is completed, the precipitate is filtered, washed and dried to obtain a precursor; the precursor is immersed in a sodium nitrate or magnesium nitrate solution, and then rotary evaporated, dried and roasted to obtain a roasted product; (9) The calcined product is uniformly mixed with graphite to obtain a mixture, and the mixture is pressed into tablets to obtain Na-modified copper-zinc-aluminum catalyst and Mg-modified copper-zinc-aluminum catalyst, respectively.

2. The method for preparing the modified copper-zinc-aluminum catalyst according to claim 1, characterized in that: In steps (1) and (2), the solvents of the salt solution a and the alkaline solution b include water, a first mixed solvent of water and isopropanol, and a second mixed solvent of water, n-hexane and isopropanol.

3. The method for preparing the modified copper-zinc-aluminum catalyst according to claim 2, characterized in that: The solvents of the salt solution a and the alkaline solution b are a second mixed solvent of water, n-hexane and isopropanol.

4. The method for preparing the modified copper-zinc-aluminum catalyst according to claim 1, characterized in that: In step (1), zinc nitrate Zn 2+ Al with aluminum nitrate 3+ The molar ratio is 5:1-2:

1.

5. The method for preparing the modified copper-zinc-aluminum catalyst according to claim 1, characterized in that: The aluminum nitrate in step (1), the aluminum nitrate in step (4) and the α-alumina in step (7) have an Al element content in a molar ratio of 1:1:

1.

6. A modified copper-zinc-aluminum catalyst, characterized in that: The modified copper-zinc-aluminum catalyst is prepared by the preparation method of any one of claims 1 to 5.

7. An application of a modified copper-zinc-aluminum catalyst, characterized in that: Use of the modified copper-zinc-aluminum catalyst according to claim 6 in catalyzing the preparation of organic aldehydes from organic alcohols.

8. The use of the modified copper-zinc-aluminum catalyst according to claim 7, characterized in that: The following steps are involved: Initial dehydrogenation: preheating the organic alcohol and adding it to the first dehydrogenation reactor for dehydrogenation, adding a modified copper-zinc-aluminum catalyst into the first dehydrogenation reactor to obtain an initial dehydrogenation product; Re-dehydrogenation: separating the initial dehydrogenation product into gas and liquid, and then transferring the liquid into a second dehydrogenation reactor for dehydrogenation, adding a modified copper-zinc-aluminum catalyst into the second dehydrogenation reactor to obtain a re-dehydrogenation product; Distillation: The re-dehydrogenation product is distilled to obtain an organic aldehyde.

9. The use of the modified copper-zinc-aluminum catalyst according to claim 8, characterized in that: The modified copper-zinc-aluminum catalyst added in the initial dehydrogenation step is a Na-modified copper-zinc-aluminum catalyst, and the modified copper-zinc-aluminum catalyst added in the re-dehydrogenation step is a Mg-modified copper-zinc-aluminum catalyst.

10. The use of the modified copper-zinc-aluminum catalyst according to claim 9, characterized in that: The mass ratio of the Na-modified copper-zinc-aluminum catalyst to the Mg-modified copper-zinc-aluminum catalyst is 1-3:1.

Citation Information

Patent Citations

  • Process for hydrogenating methylolalkanals

    CN101395112A

  • Copper-based catalyst and preparation method and application thereof

    CN105363456A

  • Copper-zinc-aluminum catalyst for preparing methanol through hydrogenization of CO2 and preparation method of copper-zinc-aluminum catalyst

    CN106179356A

  • Flower ball-like nickel-aluminum layered bimetal hydroxide, preparation method and applications thereof

    CN106241893A

  • Equipment and method for producing formaldehyde

    CN113600105A